DESIGN OF THE ANIMATED FILM SRI TANJUNG THROUGH THE PANATARAN TEMPLE RELIEF TRANSFER - Rahmad, Cito Yasuki; Adisukma, Wisnu (Acintya, 2024)
Research was conducted to create animation as a vehicle for the relief of Sri Tanjung in Panataran Temple as an education of cultural insight of the archipelago. The development of technology has brought changes in various aspects, one of which is education and entertainment (edutainment) media. Temple reliefs, which are one of the cultures of Indonesian literature, are starting to be less attractive to the younger generation now, especially the onslaught of foreign cultures that enter Indonesia. Preservation efforts need to be made because the temple reliefs contain local wisdom of Nusantara culture, which contains moral values that are beneficial to today's generation. By transforming the reliefs of Sri Tanjung stories in Panataran Temple into animated form, it is hoped that literacy through technological adaptation and education of Nusantara cultural insights is expected to be disseminated to the younger generation. The method of creation and presentation is carried out through stages: (1) exploration of ideas and ideas for the creation of Sri Tanjung animation creations; (2) model design to find animation designs through the outsourcing approach; and (3) the presentation of animated films to facilitate the delivery of educational messages of Nusantara cultural insights for today's generation. The results of the research are expected to be through the transfer of vehicles and technology adaptation, namely animation, the younger generation will have a reference to the extraordinarily rich cultural insights of the archipelago. So that a sense of national nationalism grows and is aware of the cultural richness of one's own nation.